2019
DOI: 10.1111/bjhp.12400
|View full text |Cite
|
Sign up to set email alerts
|

Illness Risk Representation beliefs underlying adolescents’ cardiovascular disease risk appraisals and the preventative role of physical activity

Abstract: Objectives The primary aim was to explore adolescents’ cardiovascular disease risk appraisals and establish whether they understood the preventative role of physical activity (PA). The secondary aim was to examine whether adolescents’ cardiovascular disease risk appraisal fitted with the Illness Risk Representations (IRR) framework. Design Qualitative. Methods Thirty‐one adolescents aged between 13 and 15 years participated in semi‐structured interviews. Data were analysed using Framework Analysis. Results Kno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 38 publications
0
5
0
Order By: Relevance
“…Physical activity and exercise show therapeutic properties that directly affect mental and physical health and are useful for most chronic diseases 18,19,20,21 . The significant effect of physical exercise on psychological well-being has been repeatedly demonstrated in many different fields that physical exercise reduces fear, stress, and anxiety 22,23,24,25,26,27 . The most crucial feature of exercise is its preventive/therapeutic benefits.…”
Section: Introductionmentioning
confidence: 98%
“…Physical activity and exercise show therapeutic properties that directly affect mental and physical health and are useful for most chronic diseases 18,19,20,21 . The significant effect of physical exercise on psychological well-being has been repeatedly demonstrated in many different fields that physical exercise reduces fear, stress, and anxiety 22,23,24,25,26,27 . The most crucial feature of exercise is its preventive/therapeutic benefits.…”
Section: Introductionmentioning
confidence: 98%
“…In this context, physical activity plays a key role in promoting an active and healthy lifestyle in students, with multiple academic, psychosocial, and sport-physical benefits [ 7 , 8 ]. Moderate physical activity generates a multitude of benefits such as reducing cardiovascular diseases [ 9 , 10 ] and gradually lowering levels of obesity and overweight [ 11 ]. In addition, in the cognitive sphere, active lifestyles significantly reduce stress and anxiety levels, improving mood and promoting socioaffective and emotional self-regulation, self-esteem, and well-being [ 12 , 13 , 14 , 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…These findings supported the importance of marked reference and cut-off point, when reporting accurate levels of CVD risk perception. Nonetheless, risk underestimation (too optimistic) had more detrimental influence on health behaviors toward CVD prevention, such as the adherence of medication ( 40 ), and lifestyle modifications ( 47 , 48 ), so as to increase the absolute risk of CVD event. We also revealed that risk underestimation was particularly prevalent among individuals with high CVD risk.…”
Section: Discussionmentioning
confidence: 99%